Adaptive myopia. Part 1. Actuating mechanisms of optic axis growth in the incremental retinal defocus theory (Ukrainian Journal of Ophthalmology, 2026)
The modern theory of acquired myopia (the theory of retinal defocus) is being considered against the backdrop of the global pandemic forecast: about 5 billion by 2050 year. The inconsistency of tincremental retinal defocus theory in part of the proposed executive mechanisms has been revealed. Until the regulations for visual work are absent, the issues of video ecology and total prevention of acquired myopia should take the first place in the fight against the myopia pandemic.
Keywords: adaptation; acquired myopia; defocus theory; video ecology; visual performance; control mechanisms of accommodation and axial length